Controls of Biotite Zone Mineral Chemistry in Archaean Meta-Sediments near Yellowknife, Northwest Territories, Canada - RAMSAY, C. R. (Journal of Petrology, 1973)
Archaean meta-sediments near Yellowknife, Canada, exhibit a low-pressure facies series and broad metamorphic zonation round a central pluton. Meta-pelites and meta-greywackes from the biotite zone have been studied using analyses of 59 minerals and 14 rocks. Mineral compositions were controlled by both host-rock composition and metamorphic grade. Increased grade commonly imposed on the minerals a progressive compositional maturation. This involved progressive compositional change (especially in meta-greywacke biotites) and/or narrowing of compositional range (particularly in muscovites). Specific effects of increased grade are as follows. Biotites in meta-greywackes exhibit increased Mg/Fe and Na/K but decreased (Na+K) content. Biotites in meta-pelites change little except for increased AlIV/Si. The muscovites display decreasing maximum Si contents, increased AlVI at the expense of Fe and Mg, and increased Na/K. The chlorites show only a slight general increase in Mg/Fe. Bulk compositional control is manifested in various ways. In some instances minerals from subtly different rock types are perceptibly distinct; in others the pro-grade maturation trends of minerals in these rock types are different. Thus Si is more abundant in meta-greywacke biotites than in meta-pelite biotites and (Na+Ba+K) content of muscovites is greater in meta-greywackes. The observed features are used to deduce mechanisms of control by grade and bulk composition and to discuss general circumstances under which they operate.